2000
DOI: 10.1136/jnnp.69.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, folate, methylation, and monoamine metabolism in depression

Abstract: Objectives-Previous studies suggest that folate deficiency may occur in up to one third of patients with severe depression, and that treatment with the vitamin may enhance recovery of the mental state. There are, however, diYculties in interpreting serum and red cell folate assays in some patients, and it has been suggested that total plasma homocysteine is a more sensitive measure of functional folate (and vitamin B12) deficiency. Other studies suggest a link between folate deficiency and impaired metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
320
1
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(357 citation statements)
references
References 22 publications
13
320
1
9
Order By: Relevance
“…Hyperhomocysteinemia is not specific for schizophrenia, and has been reported as a risk factor for various diseases such as cardiovascular diseases, 25 neural tube defects, 45 and neuropsychiatric disorders including Alzheimer's disease, 46 Parkinson's disease 47 and depression, [48][49][50] stressing the pivotal role of the single-carbon mechanism. The pathogenic mechanisms underlying these moderate hyperhomocysteinemic diseases are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinemia is not specific for schizophrenia, and has been reported as a risk factor for various diseases such as cardiovascular diseases, 25 neural tube defects, 45 and neuropsychiatric disorders including Alzheimer's disease, 46 Parkinson's disease 47 and depression, [48][49][50] stressing the pivotal role of the single-carbon mechanism. The pathogenic mechanisms underlying these moderate hyperhomocysteinemic diseases are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, deprived intake of essential nutrition, which supply the methyl groups from methyl folate or vitamin B12 and cause hyperhomocysteinemia or high level of tHcy.HHcy in depression indicates a breakdown in the methylation of homocysteine to methionine or cysteine, taurine, and glutathione -a B6 -dependent process and causes oxidative stress resulting in neurological and vascular damage and lead to disturbance in the optimal biosynthesis of neurotransmitters and cell signalling or cell repair and also disturbed the level of MAO in brain, its higher concentration as neurotoxic [24]. It is associated with various cardiovascular and other neurologicaldisorders, including cognitive impairment and dementia conversely, accumulation of tHcy involved in the path physiology of depression and reduces the level of neurotransmitters such as serotonin, dopamine, noradrenalin, and γ aminobutyric acid (GABA) are often associated with depression [10,[12][13][14]25,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have supported the essential supplements (nutrients) are involved in mood regulation and suggest a potential role for supplemental nutrients in mitigating the symptoms of depression. Sometimes tyrosine acts as a precursor to phenylalanine and are converted into dopamine and norepinephrine [2,12,[29][30][31]. Some other studies have suggested the amino acids tryptophan, tyrosine, phenylalanine, and methionine are often helpful in treating many mood disorders including depression through increasing the concentration of monoamines in the brain [11,14,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…있는 것을 보여주고 있다 (Bell IR et al, 1991;Bottiglieri T et al, 2000). 또한 우울증이 있는 사람이 허혈성 심질환으로 사망하는 비율이 높은 이유가 혈중 호모시스테인 농도가 높은 것일 수 있다는 연구도 있으나 (Surtees PG et al, 2008) 아직까지 호모시스테인이 직접적으로 우울증의 원인인지 는 아직 불분명한 것으로 알려져 있다 (Bottiglieri T, 2005).…”
Section: Reynolds Et Al(1970and1984)에 의해 호모시스테인의 메틸화 경로와 우울증과의 관계가 처음으unclassified